2007
DOI: 10.1038/sj.jes.7500553
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative asbestos exposure for US automobile mechanics involved in brake repair (circa 1950s–2000)

Abstract: We analyzed cumulative lifetime exposure to chrysotile asbestos experienced by brake mechanics in the US during the period 1950-2000. Using Monte Carlo methods, cumulative exposures were calculated using the distribution of 8-h time-weighted average exposure concentrations for brake mechanics and the distribution of job tenure data for automobile mechanics. The median estimated cumulative exposures for these mechanics, as predicted by three probabilistic models, ranged from 0.16 to 0.41 fibers per cubic centim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Several studies have reported airborne asbestos concentrations during automotive repair; some have evaluated short-term, specific tasks, such as opening boxes of asbestos-containing brakes and clutches (Jiang et al, 2008;Madl et al, 2008) or brake grinding (Richter et al, 2009), while others have measured time-weighted average (TWA) asbestos concentrations throughout an entire brake job (Blake et al, 2003;Johnson et al, 1979;Roberts, 1980a,b;Roberts and Zumwalde, 1982;Weir et al, 2001). Using job tenure data for US automotive mechanics, Finley et al (2007) estimated that median cumulative lifetime asbestos exposures ranged from 0.16 to 0.41 fiber/cc-year for facilities with no dust-control procedures (1970s), and from 0.010 to 0.012 fiber/cc-year for those employing engineering controls in the later years (1980s). These estimates are consistent with, but generally slightly lower than, the figures that have been reported for European mechanics (Finley et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have reported airborne asbestos concentrations during automotive repair; some have evaluated short-term, specific tasks, such as opening boxes of asbestos-containing brakes and clutches (Jiang et al, 2008;Madl et al, 2008) or brake grinding (Richter et al, 2009), while others have measured time-weighted average (TWA) asbestos concentrations throughout an entire brake job (Blake et al, 2003;Johnson et al, 1979;Roberts, 1980a,b;Roberts and Zumwalde, 1982;Weir et al, 2001). Using job tenure data for US automotive mechanics, Finley et al (2007) estimated that median cumulative lifetime asbestos exposures ranged from 0.16 to 0.41 fiber/cc-year for facilities with no dust-control procedures (1970s), and from 0.010 to 0.012 fiber/cc-year for those employing engineering controls in the later years (1980s). These estimates are consistent with, but generally slightly lower than, the figures that have been reported for European mechanics (Finley et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Using job tenure data for US automotive mechanics, Finley et al (2007) estimated that median cumulative lifetime asbestos exposures ranged from 0.16 to 0.41 fiber/cc-year for facilities with no dust-control procedures (1970s), and from 0.010 to 0.012 fiber/cc-year for those employing engineering controls in the later years (1980s). These estimates are consistent with, but generally slightly lower than, the figures that have been reported for European mechanics (Finley et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…6 Other studies have concluded that heavy vehicles brake mechanics are exposed to asbestos concentrations in compliance with the US Occupational Safety and Health Administration personal exposure limit (US OSHA PEL) of 0.1 f/cm 3 , and that they are not at excessive risk of developing asbestos-related diseases. [7][8][9][10][11] All these studies were conducted in high-income countries, especially in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Tel: þ33147107754; fax: þ33147107768; e-mail: jacques.ameille@rpc.aphp.fr of asbestos fibers during brake or clutch repair show disagreement (Rohl et al, 1976;Rodelsperger et al, 1986;Plato et al, 1995;Paustenbach et al, 2003;Finley et al, 2007;Blake et al, 2008;Cohen and Van Orden, 2008;Jiang et al, 2008), contributing to uncertainties about the level of risk of asbestos-related diseases in automobile mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, based on dust measurements in 76 service stations and the occupational histories of 210 vehicle mechanics with an average duration of employment of 21 -10 years, a mean cumulative exposure to asbestos was estimated to be 0.54 -1.1 f ml À1 Â years for car mechanics (Rodelsperger et al, 1986). Finley et al, 2007 recently developed estimates of cumulative chrysotile exposures experienced by automobile mechanics working with brakes and manual clutches. They reported that the 95th percentile and 99th percentile cumulative exposures for vehicles mechanics in the 1970s were 2.0 and 5.7 f ml À1 years, respectively.…”
mentioning
confidence: 99%